Japanese fashion cultures dress and gender in contemporary Japan - Monden, Masafumi (Bloomsbury, 2015)
"From rococo to Edwardian fashions, Japanese street style has reinvented many western dress styles, reinterpreting and altering their meanings and messages in a different cultural and historical context. This wide ranging and original study reveals the complex exchange of styles and what they represent in Japan and beyond, contesting common perceptions of gender in Japanese dress and the notion that non-western fashions simply imitate western styles. Through case studies focussing on fashion image consumption in style tribes such as Kamikaze Girls, Lolita, Edwardian, Ivy Style, Victorian, Romantic and Kawaii, this ground-breaking book investigates the complexities of dress and gender and demonstrates the flexible nature of contemporary fashion and style exchange in a global context. Japanese Fashion Cultures will appeal to students and scholars of fashion, cultural studies, gender studies, media studies and related fields."-- Provided by publisher.